2021
DOI: 10.1021/jacs.1c04719
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Enantioselectivity and Diastereoselectivity in Radical Cascade Cyclization for Construction of Bicyclic Structures

Abstract: Radical cascade cyclization reactions are highly attractive synthetic tools for the construction of polycyclic molecules in organic synthesis. While it has been successfully implemented in diastereoselective synthesis of natural products and other complex compounds, radical cascade cyclization faces a major challenge of controlling enantioselectivity. As the first application of metalloradical catalysis (MRC) for controlling enantioselectivity as well as diastereoselectivity in radical cascade cyclization, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 126 publications
1
21
0
Order By: Relevance
“…More recent examples from the Zhang group revealed that four-membered cyclic ketones also can be constructed in an enantioselective manner by a metalloradical catalyzed HAA and rebound sequence as shown in Scheme a . The related radical cascade reaction also allows for the enantioselective synthesis of bicyclic compounds illustrated in Scheme b . The enantioselectivities of these reactions again seem to be largely controlled by the hydrogen bonding interactions between the substrate(s) and chiral HB donors in the second coordination sphere of the catalyst.…”
Section: Substrate Orientation By Hydrogen Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent examples from the Zhang group revealed that four-membered cyclic ketones also can be constructed in an enantioselective manner by a metalloradical catalyzed HAA and rebound sequence as shown in Scheme a . The related radical cascade reaction also allows for the enantioselective synthesis of bicyclic compounds illustrated in Scheme b . The enantioselectivities of these reactions again seem to be largely controlled by the hydrogen bonding interactions between the substrate(s) and chiral HB donors in the second coordination sphere of the catalyst.…”
Section: Substrate Orientation By Hydrogen Bondingmentioning
confidence: 99%
“…453 The related radical cascade reaction also allows for the enantioselective synthesis of bicyclic compounds illustrated in Scheme 56b. 454 The enantioselectivities of these reactions again seem to be largely controlled by the hydrogen bonding interactions between the substrate(s) and chiral HB donors in the second coordination sphere of the catalyst.…”
Section: Radical-type Carbene and Nitrene Transfer Reactionsmentioning
confidence: 99%
“…Regarding substation on the alkyne group, electron-neutral and -rich aryl groups were compatible, delivering the corresponding bicyclic products in excellent yield with high enantioselectivity (8, 12, 13, 14). Substrates bearing haloarenes successfully participated in the reaction (6,7,11), producing a series of products that could be readily further functionalized via cross-coupling. Electron-poor aryl groups were also compatible (10,11), albeit giving marginally decreased yield and enantioselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a cobaltcatalyzed asymmetric radical cascade cyclization of 1,6-enynes with diazo compounds reported by Zhang and coworkers, precise selectivity control was achieved through fine-tuning of the structure of D2symmetric chiral amidoporphyrin ligands, enabling the construction of multisubstituted cyclopropane-fused tetrahydrofurans with excellent stereoselectivity. [6] Despite these advances, the development of new and highly effective metal-based chiral catalysts for controlling the stereoselectivity of radical cascade cyclization reactions remains an important objective in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The prominent catalytic performance of Cytochrome P450 enzyme has prompted the development of a vast number of biomimetic metalloporphyrin catalysts, 1 which can react with the carbene precursor to form metalloporphyrin carbene complexes. 2 Metalloporphyrin carbene complexes can undergo C–H insertion, 3 cyclopropanation, 4 etc . to generate C–C products.…”
Section: Introductionmentioning
confidence: 99%